POLITENESS STRATEGIES IN THE “ENGLISH FOR NUSANTARA”: A CONTENT ANALYSIS - Zelika, Ribka; Suharjito, Bambang; Fitriani, Ika (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
One of the essential components of communication is using politeness strategies to maintain interpersonal relationships and make them effective and efficient. Thus, inserting elements of politeness into the dialogue within textbooks can facilitate students' understanding of the application of polite language so that they can use it later as a reference to practice in everyday communication. Therefore, this study aims to figure out politeness strategies in the dialogues of the